(untitled) (Kinesiology, 2021)
The aim was to identify the relationship between the physical self-concept profile and human flourishing in physically active women, including the validation of the human flourishing scale, which had not been validated yet to the Spanish context. Five hundred eighty (N = 580) women, aged between 18 and 65 years (M = 37.13; SD = 12.56 years) completed the following questionnaires: Human Flourishing (FH), Physical Self-Perception Profile (PSPP), and Habitual Physical Activity in the last six months. After the structural regression analysis, we were able to demonstrate that the scale of human flourishing presented adequate psychometrics with a Cronbach’s alpha of .83 and a CCI of .90. Through the cluster analysis we were able to present two self-concept profiles and the reliability indexes were satisfactory: the profile of high physical self-concept was higher in women with greater human flourishing [F (1, 579) = 11.75, p<.001, η2=.02] and higher levels of physical exercise [F (1, 579) = 11,19, p<.001, η2=.01] compared to the group with a low physical self-concept. We believe that these variables have a strong influence on the personal adjustment of women and should be addressed through preventive intervention for disorders related to an individual’s distress. Key words: health, gender, flourishing, physical activity, life satisfaction